2019
DOI: 10.23960/jipt.v7i1.p173-179
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Karkas Dan Persentase Lemak Abdominal Itik Tegal Jantan Dengan Sistem Pemeliharaan Intensif Dan Semi Intensif Di KTT Bulusari Pemalang

Abstract: The aims of this study was to determine the differences in intensive and semi-intensive rearing systems on body weight, carcass weight, percentage of abdominal fat, and relative income for producing carcasses of Male Tegal duck in KTT Bulusari, Pemalang. The study was conducted on April - May 2018, in Bulusari farmer group’s farm at Bulu Village, Petarukan, Pemalang District, and Central Java. The material used in this study was male Tegal ducks from 10 farmers at the Bulu Village with the object were in Petar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Based on the standard carcass weight classification as described in the material and method section, it can be explained that the carcass weight of local male ducks circulating in traditional markets on the islands of Lombok and Sumbawa, which are included in the large category reaches 8.33±14.43%, the medium type is 10.42±13.01%, while with a small category of 81.25 ± 27.24%. The results of the study are in line with the study of [28] reported that local male ducks fed with Indigofera zollingeriana leaf meal and lemuru fish oil at a level of 5.5% with a slaughter age of 34 weeks produced a relatively small carcass weight, because the carcass weight was less than 1 kg (928.33 g).…”
Section: Classification Of Carcass Weight and Qualitysupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the standard carcass weight classification as described in the material and method section, it can be explained that the carcass weight of local male ducks circulating in traditional markets on the islands of Lombok and Sumbawa, which are included in the large category reaches 8.33±14.43%, the medium type is 10.42±13.01%, while with a small category of 81.25 ± 27.24%. The results of the study are in line with the study of [28] reported that local male ducks fed with Indigofera zollingeriana leaf meal and lemuru fish oil at a level of 5.5% with a slaughter age of 34 weeks produced a relatively small carcass weight, because the carcass weight was less than 1 kg (928.33 g).…”
Section: Classification Of Carcass Weight and Qualitysupporting
confidence: 89%
“…The difference between intensive and semi-intensive rearing systems is that the place where the maintenance and fulfillment of feed needs for ducks greatly affects the growth (body weight) and production [28]. Furthermore, it was said that the male Tegal ducks reared semi-intensively for 42 days had a bodyweight of 766.60 g, while those reared intensively were 994.28 g. Magelang ducks kept semi-intensively for 6 months had a bodyweight of 1.683 g, while the bodyweight of Magelang ducks kept intensively for 6 months was 1.683 g [26].…”
Section: The Proportion Of Body Parts Of Local Male Ducksmentioning
confidence: 99%
“…The minimum mean pancreatic weight recorded was 0.22 ± 0.03%, whereas the maximum mean pancreatic weight seen was 0.26 ± 0.04%. According to [32] the typical weight range of the pancreas is within 0.26 to 0.44 grams. According to this assertion, the weight of the pancreas in the therapy was deemed to be of low magnitude, as it fell within the range of 0.22 to 0.26 grams on average.…”
Section: Figure 2 Data On the Average Effect Of Treatment On The Perc...mentioning
confidence: 99%